Flood Modelling For Small Urban Catchment Of Sungai Raja, Alor Setar, Kedah - Ghani, Nor Zaimah Che (2014)
Malaysia is among countries that faces potential flooding problems due to rapid development, improper river management and climate change. Flood modelling was carried out within the sungai raja catchment in alor setar city. The study area is prone to flood due to its flat and low elevation. Gep was used for statistical analysis and hourly rainfall analysis shows that design rainfall from msma 2 is reliable to be used in simulation. Hydro logic and hydraulic models were used in this study with the assistance of arcview gis. Arcview gis was used to develop geometric data files require by hec-ras and preparation of basin model required by hec-hms. Hydro logic modelling was used to produce the flow hydrograph from rainfall events, as an input in hydraulic modelling. Two calibrations to represent wet and after rain condition were carried out. In order to predict the impact of land use changes to flood behaviour for sungai raja system, a scenario was created for the model simulation which is 80% of a sub-basin is fully developed and 20 % is vegetated land use.